The Environmental Public Mind Behavior of Undergraduate Students - Kannika Sookngam,; Prayoon Wongchantra,; Suparat Ongon,; Likhit Junkaew,; Uraiwan Praimee,; Phanadda Ritsumdaeng,; Surasak Kaeongam,; Thongchai Pronyusri,; Kuantean Wongchantra,; Phanat Phothibat,; Wutthisak Bunnaen,; Pitinuts Sailabat,; et al. (Journal of Educational Issues, 2024)
This research aimed to study the environmental public mind behavior of undergraduate students and compare the environmental public mind behavior of undergraduate students of different gender and year level. The sample used in the research were 230 students of 1-4 years in the Environmental Education program, Faculty of Environment and Resource Studies, Mahasarakham University, being selected by voluntarily sampling. The research tools were questionnaires on environmental public mind behavior. The statistics used for data analysis were frequency, percentage, mean, standard deviation, and hypothesis testing using correlation and One-Way ANOVA. The result was found that; environmental public mind behavior was to: environmental public mind model (x̄ = 3.93), cultivating environmental responsibility (x̄ = 3.83), environmental conservation (x̄ = 3.81), environmental sacrifice (x̄ = 3.80), environmental sustainable development (x̄ = 3.74) and environmental participation respectively (x̄ = 3.65). The relationship level of environmental public mind behavior of students in all 6 aspects was positively correlated statistically significant at the .05 level. There was no difference in environmental public mind behavior of students of different gender and year level.